Evaluasi kinerja staf UPT perpustakaan UNJA menggunakan analisis diskriminan - Affan Malik; Fuldiaratman Fuldiaratman; Bunga Mardhotillah Bunga; Hermanetty Hermanetty (Jurnal Paradigma Ekonomika, 2021)
UPT Library UNJA is a Service Unit whose duties and functions are closely related to science, education, and development, especially in managing and providing various literacy, references, information, and documentation. The performance of its management staff strongly influences the management system of the UNJA Library UPT. Ideally, the performance measurement of UPT Library staff can refer to the applicable ISO standards. However, a more comprehensive performance evaluation based on the specifics and factors that affect the performance of UPT UNJA staff and the classification of staff performance evaluation is critical. UPT Library Staff Performance Evaluation based on ISO 11620: 2014 Document concludes that staff performance is good. On the other hand, the application of discriminant analysis of the performance of the Jambi University Library UPT staff analyzed 15 variables with Performance Quality as a variable consisting of two categories, namely Good and Very Good. The Stepwise Method in Discriminant Analysis reduces several independent variables so that the most significant variables in this analysis are the ability to make decisions (X6), Honesty (X8), Initiative in the line of Tasks (X9), and Skill Problem Solver (X11).